Calle Real revitalization program and public's level of acceptance - Agusila, Annielee Z.; Belandres, Arlene D.; Dumalaos, Kristine Vi V.; Guazo, Harold D.; Ober, Jenefel M.; Odron, Hepsefyll Ann C.; Sumongcad, Elsie B.
The Iloilo City government had recently initiated its Revitalization Program in the Central Business District (CBD), which includes the Calle Real. The program is focused on the implementation of its specific plans; the arcaded sidewalk, recreation of the original facade, relocation of sidewalk vendors, standardized umbrella cafes. In line with this, this study was conducted to find out the levels of acceptance of the general public on the said Revitalization Program, which includes the legacy-building owners, tenants, sidewalk vendors, and the customers. Indicators that would affect the respondents' willingness to accept the program are also identified. the study made use of historical and descreptive research designs. Data were gathered through library research, structured interviews and questionnaires. The results of the study showed that awareness on the program does not affect the level of acceptance of all types of respondents. the desirability of specific plans identified in the program affects the level of acceptance of tenants and customers. Attitude towards government projects also influence respondents' willingness to accept. In general, tenants and customer respondents showed a high level of acceptance. Sidewalk vendors on the other hand, are unwilling to accept the program because of their proposed relocation. Legacy-buillding owners are generally undecided to accept the program. Historical research showed that most buildings, classified as legacy/heritage buildings were constructed in early 1900's. Other historical data such as original owners and historical significance were ot known because of the difficulty in locating and interviewing the owners.